2008
DOI: 10.1161/circulationaha.107.752006
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Health Status in Coronary Heart Disease in the United States

Abstract: Background-Coronary heart disease (CHD) affects 15.8 million Americans. However, data on the national impact of CHD on health-related quality of life, particularly among people of different age, sex, racial, and ethnic groups, are limited. Methods and Results-Using

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
114
5
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(134 citation statements)
references
References 28 publications
(18 reference statements)
8
114
5
6
Order By: Relevance
“…The composite index of EQ-5D was 0.72 (SD 0.19), which is lower than in the international analysis of high-risk patients in the EPA-Cardio study, where it was found to be 0.78 (SD 0.19) (23) and lower than in other studies, even for CVD patients (24). On the other hand, coronary patients in the national analysis of Epa-Cardio data showed lower HRQoL in coronary patients, measured by EQ-5D VAS scale (58.6±19.9) (25), compared to high risk patients in The association of isolated risk diseases, such as hypertension, is conflicting and shows no relationship with HRQoL (26,27) or contributes to a lower HRQoL (28).…”
Section: Discussioncontrasting
confidence: 64%
“…The composite index of EQ-5D was 0.72 (SD 0.19), which is lower than in the international analysis of high-risk patients in the EPA-Cardio study, where it was found to be 0.78 (SD 0.19) (23) and lower than in other studies, even for CVD patients (24). On the other hand, coronary patients in the national analysis of Epa-Cardio data showed lower HRQoL in coronary patients, measured by EQ-5D VAS scale (58.6±19.9) (25), compared to high risk patients in The association of isolated risk diseases, such as hypertension, is conflicting and shows no relationship with HRQoL (26,27) or contributes to a lower HRQoL (28).…”
Section: Discussioncontrasting
confidence: 64%
“…Patients suffering from CHD are likely to have an impaired QoL, due to pain, anxiety, functional and social limitations (5)(6)(7)(8). Although still under debate, several studies have observed a relationship between QoL, depression, anxiety and worse long-term health outcomes (9)(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Most studies assessing HRQoL in patients with CAD have been carried out in the United States (6)(7)(8) , European countries (5,(9)(10) and a smaller number of studies have been conducted in countries like Canada (11) . Their assessments of HRQoL have been largely based on the Medical Outcomes Study: 36-Item Short Form Survey (SF-36) questionnaire and researchers have conducted these assessments at different time points after first hospital admission due to CAD (7,(9)(10)(11)(12)(13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%
“…Based on a literature search and our clinical experience, we decided to explore the following question: are there any differences in HRQoL in patients admitted for the first time due to ACS (AMI and UA) according to gender and prior treatment for any other cardiovascular condition? Some studies have reported lower scores of HRQoL among women with CAD (6,8,11,13,16) and other cardiovascular conditions (14) .…”
Section: Introductionmentioning
confidence: 99%